2023
DOI: 10.1002/smll.202301288
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Ligand and Composition Effects: Morphology‐Tailorable Pt–Bi Bimetallic Aerogels for Enhanced (Photo‐)Electrocatalysis

Abstract: Metal aerogels (MAs) are emerging porous materials displaying unprecedented potential in catalysis, sensing, plasmonic technologies, etc. However, the lack of efficient regulation of their nano‐building blocks (NBBs) remains a big hurdle that hampers the in‐depth investigation and performance enhancement. Here, by harmonizing composition and ligand effects, Pt‐ and Bi‐based single‐ and bimetallic aerogels bearing NBBs of controlled dimensions and shapes are obtained by facilely tuning the metal precursors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…12 Generally, ligands or surfactants were employed to modulate the size and shape of NPs by controlling the growth. 13–16 Furthermore, in order to stabilize and improve the catalytic efficiency of the catalyst, phosphines or nitrogen-based ligands are often required to bind at the surface of NPs by regulating the steric and electronic parameters. 17–23 For example, Lipshutz et al reported phosphine ligand-based Pd NP catalysts for the Suzuki–Miyaura reaction in aqueous micelles by regulating steric effects and electronic structures at the ligand–metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…12 Generally, ligands or surfactants were employed to modulate the size and shape of NPs by controlling the growth. 13–16 Furthermore, in order to stabilize and improve the catalytic efficiency of the catalyst, phosphines or nitrogen-based ligands are often required to bind at the surface of NPs by regulating the steric and electronic parameters. 17–23 For example, Lipshutz et al reported phosphine ligand-based Pd NP catalysts for the Suzuki–Miyaura reaction in aqueous micelles by regulating steric effects and electronic structures at the ligand–metal interface.…”
Section: Introductionmentioning
confidence: 99%